Renal Denervation Prevents Atrial Arrhythmogenic Substrate Development in CKD. Issue 6 (8th February 2022) - Hohl, Mathias; Selejan, Simina-Ramona; Wintrich, Jan; Lehnert, Ulrike; Speer, Thimoteus; Schneider, Clara; Mauz, Muriel; Markwirth, Philipp; Wong, Dickson W.L.; Boor, Peter; Kazakov, Andrey; Mollenhauer, Martin; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: In patients with chronic kidney disease (CKD), atrial fibrillation (AF) is highly prevalent and represents a major risk factor for stroke and death. CKD is associated with atrial proarrhythmic remodeling and activation of the sympathetic nervous system. Whether reduction of the sympathetic nerve activity by renal denervation (RDN) inhibits AF vulnerability in CKD is unknown. Methods: Left atrial (LA) fibrosis was analyzed in samples from patients with AF and concomitant CKD (estimated glomerular filtration rate [eGFR], <60 mL/min per 1.73 m 2 ) using picrosirius red and compared with AF patients without CKD and patients with sinus rhythm with and without CKD. In a translational approach, male Sprague Dawley rats were fed with 0.25% adenine (AD)-containing chow for 16 weeks to induce CKD. At week 5, AD-fed rats underwent RDN or sham operation (AD). Rats on normal chow served as control. After 16 weeks, cardiac function and AF susceptibility were assessed by echocardiography, radiotelemetry, electrophysiological mapping, and burst stimulation, respectively. LA tissue was histologically analyzed for sympathetic innervation using tyrosine hydroxylase staining, and LA fibrosis was determined using picrosirius red. Results: Sirius red staining demonstrated significantly increased LA fibrosis in patients with AF+CKD compared with AF without CKD or sinus rhythm. In rats, AD demonstrated LA structural changes with enhanced sympathetic innervation compared with control. In AD, LA enlargement was associated with prolonged duration of induced AF episodes, impaired LA conduction latency, and increased absolute conduction inhomogeneity. RDN treatment improved LA remodeling and reduced LA diameter compared with sham-operated AD. Furthermore, RDN decreased AF susceptibility and ameliorated LA conduction latency and absolute conduction inhomogeneity, independent of blood pressure reduction and renal function. Conclusions: In an experimental rat model of CKD, RDN inhibited progression of atrial structural and electrophysiological remodeling. Therefore, RDN represents a potential therapeutic tool to reduce the risk of AF in CKD, independent of changes in renal function and blood pressure.